Mathematical Anxiety Analysis Among JHS Students in Makassar and Malang - Putra, Muh. Hidayatullah Dwi; Purwanto, Purwanto; Kusumasari, Vita (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2025)
Research shows that female students are generally more susceptible to mathematics anxiety than male students, although some studies have found similar or higher levels of anxiety among males in certain contexts. The research gap lies in the need for further exploration of how the interaction between gender and geographical location influences the level of mathematics anxiety. This study aims to analyze the level of mathematical anxiety among junior high school students in Makassar and Malang, focusing on various aspects of mathematics anxiety and comparing these levels based on gender. The research method employed is a quantitative descriptive approach, involving 86 students from junior high schools in both cities. The instruments used include a mathematical anxiety identification test and a questionnaire that measures the four main aspects of anxiety. The results indicate that, overall, the mathematical anxiety of students in both cities falls within the moderate category across all analyzed aspects. Female students tend to experience higher levels of anxiety compared to male students, particularly in Malang, while in Makassar, male students exhibit slightly higher mathematical anxiety in several categories. This study highlights the need for self-regulated learning to reduce mathematics anxiety in both male and female students.